UV-Visible radiation modulation abilities of photon up-converting nanocapsules integrated with an oscillatory reaction. Issue 23 (1st June 2022) - Quaglia, Giulia; Bartolomei, Beatrice; Gentili, Pier Luigi; Latterini, Loredana
Abstract : Oil-in-silica capsules enable triplet–triplet annihilation radiation up-conversion in air equilibrated conditions and their use to achieve controlled intensity modulated emission. Abstract : Radiation up-conversion through the triplet–triplet annihilation mechanism has been widely studied, mostly in solution and under de-aerated conditions. We propose oil-in-silica up-converting nanocapsules resulting in a robust solid-like material able to generate blue up-converted emission and preserve the red phosphorescence of the sensitizer under atmospheric conditions. The core phase consists of oleic acid containing the up-converting molecular pair, platinum octa-ethyl-porphyrin and 9, 10-diphenyl-anthracene; the silica shell having 10–15 nm thickness acts as a protective barrier and compartmentalizes the organic molecules. The up-converted emission is measured from silica nanocapsule powder or in aqueous suspensions using an incoherent and low power density (363 μW cm −2 ) source. The robustness of the oil-in-silica structures is tested in the acidic and oxidative solution of the oscillatory Belousov–Zhabotinsky (BZ) reaction. The BZ reaction gives rise to a modulated optical density in the UV-region. The modulated UV radiation is absorbed by the chromophores in the nanocapsules delivering periodic emissions of the capsules, which are monitored in terms of intensity amplitude and periodicity. The solidness of the nanocapsules enables employing them in a wet chemical formulation to be exposed simultaneously to the BZ-modulated UV radiation and to the steady-state Vis radiation, obtaining multiple output luminescence signals. Furthermore, the impact of simultaneous excitations empowers discussions of the intensity changes in terms of efficiencies of triplet energy transfer and establishing UC-nanostructured materials for optical communication applications.